STRUKTUR KOMUNITAS GASTROPODA DI SUNGAI DIGOEL DISTRIK EDERA KABUPATEN MAPPI - Nova S. Monika; Sendy Lely Merly; FX Kakumun (Faculty of Agriculture Musamus University, 2019)
Edera District is the one of separated districts of six districts in the Mappi Regency. The increasing of community population has caused an increase activities in resource utilization, especially in the Digoel River area. As a result of excessive utilization activities can potentially cause pollution that threatens the existence and continuity of organisms such as Gastropods. This study aims to determine the community structure of Gastropods in the Digoel River in Edera District, Mappi Regency. The study lasted for 3 months from January to March 2018 by using the survey method and reviewing several variables including: diversity index, uniformity index and dominance index. The results showed that at the 3 observation stations the total sample was 1233 individuals. The highest diversity index value was at station II, namely itlic. and lowest was at station I Ellobium chinense species. Uniformity index shows that the number of uniformity is not evenly distributed in all three stations due to the occurrence of certain types of dominance. Keywords: Gastropoda; Community Structure; Digoel River; Mappi Regeucy Regeucy